2012
DOI: 10.1155/2012/979751
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variation May Compensate for Decreased Genetic Variation with Introductions: A Case Study Using House Sparrows (Passer domesticus) on Two Continents

Abstract: Epigenetic mechanisms impact several phenotypic traits and may be important for ecology and evolution. The introduced house sparrow (Passer domesticus) exhibits extensive phenotypic variation among and within populations. We screened methylation in populations from Kenya and Florida to determine if methylation varied among populations, varied with introduction history (Kenyan invasion <50 years old, Florida invasion ~150 years old), and could potentially compensate for decrease genetic variation with introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(116 citation statements)
references
References 44 publications
4
112
0
Order By: Relevance
“…In most wild animal populations examined to date, there has been an excess of DNA methylation variation relative to genetic variation (Massicotte et al, 2011;Mor an & P erez-Figueroa, 2011;Liu et al, 2012;Massicotte & Angers, 2012;Schrey et al, 2012;Liebl et al, 2013;Skinner et al, 2014;Wenzel & Piertney, 2014). First investigations into epigenetic variation in wild animal populations involved the salmonid, Oncorhynchus mykiss (Blouin et al, 2010).…”
Section: Population Epigenetics In the Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…In most wild animal populations examined to date, there has been an excess of DNA methylation variation relative to genetic variation (Massicotte et al, 2011;Mor an & P erez-Figueroa, 2011;Liu et al, 2012;Massicotte & Angers, 2012;Schrey et al, 2012;Liebl et al, 2013;Skinner et al, 2014;Wenzel & Piertney, 2014). First investigations into epigenetic variation in wild animal populations involved the salmonid, Oncorhynchus mykiss (Blouin et al, 2010).…”
Section: Population Epigenetics In the Wildmentioning
confidence: 99%
“…clonal fish, Massicotte et al, 2011;Massicotte & Angers, 2012) or bottlenecks following invasion (e.g. house sparrows, Schrey et al, 2012;Liebl et al, 2013). Following from classic investigations in plants (Cubas et al, 1999;Kalisz & Purugganan, 2004), these studies provide the first indications from animals that DNA methylation may sometimes act independently from underlying genetic variation, and facilitate a clearer evaluation of the consequences of epigenetic variation.…”
Section: The Evolutionary Potential Of Epigenetic Variationmentioning
confidence: 99%
“…Just as a population may contain standing genetic variation for plasticity, it could also carry standing epigenetic variation (SEV) for plasticity (e.g. Wong et al, 2005;Johannes et al, 2009;Schrey et al, 2012), with SEV being caused by variation in individuals' past experiences of their environment. A population exposed to a novel environment may therefore be phenotypically similar to its ancestral population, but have reduced variation in SEV for the loci involved.…”
Section: Fig 2 Overcoming Maladaptive Plasticity Through (A) and (B)mentioning
confidence: 99%
“…Several studies in natural populations of plant and animal species revealed correlations between genome-wide patterns of DNA methylation with environmental variation (Paun et al 2010;Schrey et al 2012;Schulz et al 2014Raj et al 2011;Hafer et al 2011;Dombrovsky et al 2009;Richards et al 2012;Lira-Medeiros et al 2010). Also chapter 5 of this thesis has revealed some regional differentiation in the epigenetic profiles in natural populations of apomictic dandelions.…”
Section: Introductionmentioning
confidence: 92%
“…Studies in natural populations of sexually reproducing plants demonstrated a correlation between genetic and epigenetic markers while a proportion of epigenetic variation showed sequence-independent differentiation Herrera & Bazaga 2010;Schulz et al 2014). Also in natural populations of animal species and in nectar inhabiting yeast some evidence for distinct and ecologically relevant epigenetic patterns was found Schrey et al 2012). Our study differs from these and related studies because our study was not based directly on field-collected material (or vegetatively derived offspring), but on natural DNA methylation variation that persists through apomictic seed production.…”
Section: Natural Epigenetic Variationmentioning
confidence: 98%